2021
DOI: 10.3233/nre-201606
|View full text |Cite
|
Sign up to set email alerts
|

Effects of coupling inhibitory and facilitatory repetitive transcranial magnetic stimulation on motor recovery in patients following acute cerebral infarction

Abstract: BACKGROUND: The treatment for patients suffering from motor dysfunction following stroke using continuous repetitive transcranial magnetic stimulation (rTMS) has the potential to be beneficial for recovery. However, the impact of explicit results on the coupling of various rTMS protocols on motor treatment in patients following acute cerebral infarction remain unexplored. OBJECTIVE: The current study aims to design a sham-controlled randomized report to explore the capability of consecutive suppressive-facilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 38 publications
1
21
0
Order By: Relevance
“…rTMS has been found to promote the recovery of exercise, learning, and memory in patients with cerebral infarction and to improve neurological damage in rats with cerebral ischemia and reperfusion [ 26 , 27 ]. In our experiments, it was found that in rats treated with rTMS, the neurological deficit scores were reduced, and the time to remove bilateral stickers and the time to cross the balance beam was reduced, which confirmed that rTMS can improve the neuromotor function of rats with experimental cerebral infarction.…”
Section: Discussionmentioning
confidence: 99%
“…rTMS has been found to promote the recovery of exercise, learning, and memory in patients with cerebral infarction and to improve neurological damage in rats with cerebral ischemia and reperfusion [ 26 , 27 ]. In our experiments, it was found that in rats treated with rTMS, the neurological deficit scores were reduced, and the time to remove bilateral stickers and the time to cross the balance beam was reduced, which confirmed that rTMS can improve the neuromotor function of rats with experimental cerebral infarction.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with that before treatment, the number of patients with severe cerebral infarction or even vascular stenosis was significantly reduced ( P < 0.05), with a gradual shift to mild vascular stenosis and a marked improvement in neurological dysfunction. It was consistent with the findings of Chen et al ( 2021 ). It was verified that the MRI image segmentation technology based on CNN algorithm can perform accurate segmentation of acute cerebral infarction lesions and improve the MRI image diagnosis effect of acute cerebral infarction.…”
Section: Discussionsupporting
confidence: 93%
“…Seventeen studies were divided into five subgroups based on the number of treatment sessions: 5 sessions, 10 sessions, 12-15 sessions, and 20 sessions. The effect sizes were as follows: (SMD, 0.35; 95% CI 0.09-0.62; P = 0.009) for 5 sessions (20,22,23); (SMD, 0.50; 95% CI −0.00-1.01; P = 0.052) for 10 sessions (38,46,49,51,52); (SMD, 1.39; 95% CI −0.98-3.75; P = 0.25) for 12-15 sessions (30,50) and (SMD, 3.73; 95% CI 1.22-6.24; P = 0.004, Supplementary Figure 2D) for 20 sessions (32).…”
Section: E Ect Of Rtms or Sham Stimulation On Fma-ue In Patients With...mentioning
confidence: 96%
“…Sub-studies were identified in sixteen studies. These studies included 2 (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31), 3 (32)(33)(34) and 4 experimental groups (35) (each group differed in terms of patient characteristics or TMS protocol) and indicated the FMA-UE scores respectively, for each subgroup separately. The mean age of patients varied from 51.0 to 74.0 years, and the mean age of controls ranged from 50.5 to 75.0 years.…”
Section: Characteristics Of the Rctsmentioning
confidence: 99%
See 1 more Smart Citation